2000
DOI: 10.1007/s100720070107
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effectiveness of acetazolamide in hindbrain hernia headache

Abstract: A 43-year-old man had been suffering from exertional headache for 10 years. Sagittal sections on magnetic resonance imaging showed a Chiari type 1 malformation and a cerebellar arachnoid cyst. This syndrome, named hindbrain hernia headache, disappeared with oral acetazolamide. This treatment should be tried in patients with hindbrain hernia headache prior to considering surgical decompression of the foramen magnum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Our patient's improvement on high dose acetazolamide provided support for consideration of this medication in other patients with keyhole aqueduct syndrome and mesencephalic cleft and suggested that manipulation of CSF synthesis or dynamics can ameliorate symptoms of keyhole aqueduct syndrome. Acetazolamide, a carbonic anhydrase inhibitor that decreases CSF production and secretion, can help improve symptoms of intracranial hypertension, 13 syringomyelia, 14 hindbrain herniation headache, 15 and Chiari malformation. 16 Furthermore, a majority of patients with keyhole aqueduct syndrome exhibit a progressive clinical course, although some have a static course.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient's improvement on high dose acetazolamide provided support for consideration of this medication in other patients with keyhole aqueduct syndrome and mesencephalic cleft and suggested that manipulation of CSF synthesis or dynamics can ameliorate symptoms of keyhole aqueduct syndrome. Acetazolamide, a carbonic anhydrase inhibitor that decreases CSF production and secretion, can help improve symptoms of intracranial hypertension, 13 syringomyelia, 14 hindbrain herniation headache, 15 and Chiari malformation. 16 Furthermore, a majority of patients with keyhole aqueduct syndrome exhibit a progressive clinical course, although some have a static course.…”
Section: Discussionmentioning
confidence: 99%